2007
DOI: 10.1590/s0034-89102006005000034
|View full text |Cite
|
Sign up to set email alerts
|

Concentração de fluoreto em arroz, feijão e alimentos infantis industrializados

Abstract: OBJECTIVE:To determine fl uoride concentrations in the typical Brazilian meal (rice with beans) and in processed infant foods, and to estimate their contribution towards dental fl uorosis. METHODS:The foods were purchased at supermarkets in the cities of Piracicaba and Campinas, Southeastern Brazil. The processed infant foods were bought in 2001 and the rice and beans in 2003, and they were analyzed immediately. Three brands of rice, three brands of beans and 36 samples of infant foods were analyzed, divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
0
2
0
5
Order By: Relevance
“…O arroz com feijão (na proporção aproximada de 2:1) é uma combinação altamente nutritiva, e é o prato típico brasileiro. No entanto, nos últimos tempos observou-se uma diminuição no seu consumo e aumento considerável no consumo de carnes 14,15 . Diante dos erros mais prevalentes nas respostas dos universitários, em relação à na pergunta que questionava sobre o porcionamento correto de frutas, 52,5% (n=52) não sabiam a sua correta recomendação diária, assim como aconteceu nas porções de hortaliças, em que 93% (n=93,9) dos avaliados também não conheciam a quantidade correta de consumo diário.…”
Section: Resultsunclassified
“…O arroz com feijão (na proporção aproximada de 2:1) é uma combinação altamente nutritiva, e é o prato típico brasileiro. No entanto, nos últimos tempos observou-se uma diminuição no seu consumo e aumento considerável no consumo de carnes 14,15 . Diante dos erros mais prevalentes nas respostas dos universitários, em relação à na pergunta que questionava sobre o porcionamento correto de frutas, 52,5% (n=52) não sabiam a sua correta recomendação diária, assim como aconteceu nas porções de hortaliças, em que 93% (n=93,9) dos avaliados também não conheciam a quantidade correta de consumo diário.…”
Section: Resultsunclassified
“…The fluoride content of the food consumed can have an important impact on the quantity of fluoride ingested [25-27]. Rice is a staple foodstuff in the diet in Thailand and is eaten from an early age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that different methods of preparation and cooking of rice can affect the final fluoride concentration [28] and even when rice is prepared with water considered to be optimally fluoridated there can be a significant effect on fluoride content and hence fluoride intake. It has been demonstrated individuals consuming a similar diet of rice and beans in an optimally fluoridated area would be subject to a dose of 0.02mmg/F/day/kg body weight – corresponding to 45% of the total intake of fluoride from foods and beverages [27]. Nevertheless, it would appear both the water used for soaking the rice and the length of time the rice is soaked have the most profound effect [7].…”
Section: Discussionmentioning
confidence: 99%
“…Se requiere más investigación para determinar si el reemplazo del consumo de agua potable fluorada por el agua embotellada sin F, pero manteniendo la exposición a las dosis contenidas en los dentífricos tiene un impacto real en la ocurrencia de caries de la población. Es importante destacar que la población que vive en una región con agua fluorada, aun cuando no consuma agua potable para beber, continúa beneficiándose por la incorporación de F cuando los alimentos son preparados con dicha agua 37 . Dada la gran disparidad en el contenido de F en las aguas disponibles en Chile, se sugiere que la concentración de F debería ser declarada en el envase de los fabricantes.…”
unclassified